The Creation of User Experience in the Policy of Enterprises as an Answer to New Trends and Changes in Customer Behaviour - Pokotycki, De (Studia Oeconomica Posnaniensia, 2017)
Technological development leads to the birth of new trends and changes in the behaviour of customers who contribute increasingly to the co-creation of the offer directed towards them (the so-called value co-creation). The traditional approach based on the study of the standard needs in the marketing department seems to give way to the one focusing in establishing the actual needs and answering the desires of potential, clearly defined buyers. A lot of companies may perceive such changes as a threat, but if used properly they can be translated into opportunities. What can be particularly helpful within that scope is the approach based on creating user experience, which is, using the knowledge from a relatively young field, the genesis of which lies in the new technologies sector. It has been taken to a significant extent from the world of marketing, resulting in convergence with it. However, the above mentioned field seems to answer better the changes taking place on modern day markets. Meeting the expectations, needs and desires of consumers with the use of user experience creation may translate to an increase in sales, better brand reception or the greater loyalty of customers. Because of noticing the nature of new trends and changes in customer behaviour, such an approach should lead to measurable benefits and, therefore, the success of many progressive companies on the market.